Advance directives from a Biolaw perspective: patient empowerment and healthcare professional participation - Fernández Campos, Juan Antonio (2024)
Starting from an interdisciplinary vision, from the perspective of biolaw, the patient's autonomy to make their own decisions is addressed, in advance and voluntarily, which must be diligently documented (informed consent) by the health professional. Likewise, the objections that could be raised to the observance of the patient's advance directives are analyzed; the scope of effectiveness of the patient's will, as well as thefuture perspectives of advance directives, in terms of weaknesses and strengths, in order to protect the dignity of people, through adequate intervention by medical personnel.